2019
DOI: 10.2217/rme-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Change of a Cohort of 570 Unproven Stem Cell Clinics in the USA Over 3 Years

Abstract: Aim: The industry of unproven stem cell clinics has rapidly mushroomed throughout the USA, posing risks to patients and the research field. In this study, the aim was to better define how this industry changes. Methods: I analyzed a large cohort of US stem cell clinic firms and their distinct clinic locations as defined in 2015–2016 for their status now in 2019. Results: About a quarter of the firms no longer marketed stem cells. Some lacked active websites, while others dropped stem cell services. Even so, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Earlier analyses indicated that unproven SCI clinics were predominately located in countries considered to have less regulatory enforcement over drugs and biologics. Since 2014, clinics marketing purported SCIs have emerged in countries with robust regulatory infrastructure within Europe, North America, Australia, and Southeast Asia ( Berger et al., 2016 ; Connolly et al., 2014 ; Knoepfler, 2019d ; Munsie et al., 2017 ; Ogbogu et al., 2018 ; Turner and Knoepfler, 2016 ). Based on online advertising, the unproven SCI market is estimated at US$2.4 billion impacting 60,000 patients annually ( International Society Cell and Gene Therapy (ISCT), 2018 ) with documented clinics in Australia, Austria, Canada, China, Colombia, Costa Rica, Dominican Republic, Germany, India, Israel, Japan, Korea, Malaysia, Mexico, the Netherlands, New Zealand, Panama, Philippines, Portugal, Russia, Spain, Thailand, Turkey, UK, US, and Ukraine.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier analyses indicated that unproven SCI clinics were predominately located in countries considered to have less regulatory enforcement over drugs and biologics. Since 2014, clinics marketing purported SCIs have emerged in countries with robust regulatory infrastructure within Europe, North America, Australia, and Southeast Asia ( Berger et al., 2016 ; Connolly et al., 2014 ; Knoepfler, 2019d ; Munsie et al., 2017 ; Ogbogu et al., 2018 ; Turner and Knoepfler, 2016 ). Based on online advertising, the unproven SCI market is estimated at US$2.4 billion impacting 60,000 patients annually ( International Society Cell and Gene Therapy (ISCT), 2018 ) with documented clinics in Australia, Austria, Canada, China, Colombia, Costa Rica, Dominican Republic, Germany, India, Israel, Japan, Korea, Malaysia, Mexico, the Netherlands, New Zealand, Panama, Philippines, Portugal, Russia, Spain, Thailand, Turkey, UK, US, and Ukraine.…”
Section: Main Textmentioning
confidence: 99%
“…The growth of the US unproven SCI market was noted to be about 570 clinics in 2015–2016 ( Turner and Knoepfler, 2016 ), about 715 in 2017–2018 ( Turner, 2018 ), and in 2019 is estimated to be about 1,000 ( Knoepfler, 2019d ). In 2017, the FDA revised their guidance on cell-based therapies, which reiterated that all human cells, tissues, and cellular- and tissue-based products (HCT/Ps) that are more than minimally manipulated and/or intended for non-homologous uses will be regulated as a drug, device, and/or biologic ( U.S. Food and Drug Administration, 2017a , 2017b ).…”
Section: Main Textmentioning
confidence: 99%
“…Many clinics currently marketing 'stem cell-based' treatments, of which there may be over 700 in the US alone [10], cite an exemption over 'minimal manipulation' and 'homologous use'. Where a human tissue or cell-based product has been minimally manipulated -for example, nothing more than centrifugation or cryopreservationand will produce the same function in the recipient as they did in the donor, it doesn't need the formal approval of the FDA.…”
Section: Minimal Manipulation… or Notmentioning
confidence: 99%
“…SARS-CoV-2 is causing lingering (months) symptoms for many patients, and studies are now underway to follow patients for at least two years in order to understand long lasting, possibly debilitating, symptoms ( 11 ). While many companies and physicians continue to use stem cells and the molecules/exosomes derived from stem cells, the vast majority of these therapeutics are unproven and often dangerous ( 12 ). Further, bringing patients into a clinical setting, especially for infectious diseases, can lead to superspreading of pathogens even in the world’s most prestigious hospitals such as the National Institute of Health hospitals in the USA ( 13 ).…”
Section: Introductionmentioning
confidence: 99%